The Heterotopia of Petersburg in the Prose of Oleg Postnov - Tyszkowska-Kasprzak, Elżbieta (Literatūra, 2025)
The article presents the image of Petersburg in the novels The Fate of Petersburg, Valerian Somov’s Night Stories, and Petersburg PM by the contemporary Russian writer Oleg Postnov. To interpret and characterize the representation of urban space in these works, the concept of ‘heterotopia’, introduced by Michel Foucault, is employed. In Postnov’s prose, the Northern capital appears as a kind of realization of Peter the Great’s phantasmagorical vision. According to the writer, Petersburg is a city-monument, a city-museum. He describes it as a city that remains unchanged since the beginning of the 19th century. Accordingly, Postnov directs the reader toward the literary depictions of Petersburg from the previous century and adopts the romantic mode of depicting the city. In portraying the city’s unique character, Postnov cites the works of A. Pushkin, N. Gogol, and F. Dostoevsky. The writer emphasizes the city’s duality and its mystical, enigmatic nature. This portrayal of the city reflects the ‘Russian soul’, which can be seen as both ambivalent and indefinite.